Spectrum of gastrointestinal perforation peritonitis in 462 consecutive patients in tertiary care institute of North India - Singh, Mahavir; Dalal, Satish; Gera, Mridul (International Surgery Journal, 2021)
Background: Gastrointestinal perforation is one of the common surgical emergencies in developing countries. The diagnosis is mainly clinical and is aided by radiological investigations. This study was designed to highlight the spectrum of hollow viscus perforation peritonitis in terms of etiology, clinical presentations, site of perforation, surgical treatment, postoperative complications, and mortality. Methods: The study was a hospital‑based observational study and included 462 patients of perforation peritonitis (diffuse or localized) who were studied retrospectively in terms of cause, site of perforation, surgical treatment, complications, and mortality. Only those patients who underwent exploratory laparotomy for management of perforation peritonitis were included. Results: Overall stomach was the most common site of perforation (33%). Ileum (26%) was the second common site of perforation. Duodenal perforations were seen in 88 (19%) cases whereas appendicular perforations were seen in 46 (10%) cases. Colonic perforations were least common. Acid peptic disease was the most common etiology of stomach perforations. Enteric fever (63%) was the most common etiology of jejuno-ileal perforation. Other causes include tuberculosis (23%), trauma (8%), malignancy (3%) and idiopathic in rest. Males were six times more commonly affected than females. Peak incidence was noted in the 2nd and 3rd decades of life. Conclusions: Spectrum of perforation peritonitis cases in developing world is different from developed countries The Western literature suggests that foreign body, ischemia, radiotherapy, diverticula, and Crohn’s disease are the main causes of perforations. In contrast to this, infection is the most common cause for perforations in developing countries.